Penerapan Pembelajaran Kombinasi Antara Blended Learning dan Peer Learning untuk Meningkatkan Kemampuan Group-Work - Nur'aini Muhassanah; Noor Sofiyati; Dwiani Listya Kartika (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
Improving student achievement and group-work ability by applying a combination of blended learning and peer learning as the aim of this research. This research was conducted in March – July 2022. This type of research is classroom action research which consists of cycles, where each cycle has 4 stages, namely: planning, implementation, observation and reflection. This research was conducted on 8 4th semester students of the mathematics study program for the 2021/2022 academic year who took the Introduction to Demographics course. Data collection techniques used are tests and observations. The results of this study are 1) improving the results of learning achievement seen from the class average value from before the study, which was 57.87 and after the study consisting of cycle I and cycle II with an average grade of 71.5 and 80.25. 2) improve the ability of student group-work in several criteria, namely: student activity in learning, better communication methods, student contributions and responsibilities to the tasks given in groups, and the ability to express opinions/ideas. This is indicated by the results of the group-work ability data which before the research students were included in the criteria of not being good (37.5%), quite good (50%), and good (12.5%). After the action, the students were categorized as quite good (12.5%), good (25%), and very good (62.5%).